2009
DOI: 10.1203/pdr.0b013e3181be79c2
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency and Renal Development in the Newborn Rat

Abstract: ABSTRACT:Iron is essential for fetal organ development, but the effect of isolated iron deficiency on nephrogenesis is unknown. Human premature infants are at risk for disrupted nephrogenesis because glomerular development is incomplete until 36-wk gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 42 publications
2
23
0
1
Order By: Relevance
“…90 A deficiency in iron can impact kidney development through fetal anaemia and hypoxia, as well as modified glucocorticoid sensitivity. 89 Zinc is an antioxidant that exhibits antiapoptotic properties.…”
Section: Maternal Micronutrient Deficienciesmentioning
confidence: 99%
“…90 A deficiency in iron can impact kidney development through fetal anaemia and hypoxia, as well as modified glucocorticoid sensitivity. 89 Zinc is an antioxidant that exhibits antiapoptotic properties.…”
Section: Maternal Micronutrient Deficienciesmentioning
confidence: 99%
“…Furthermore, exposure to a maternal low-protein diet during lactation in rat also compromises nephrogenesis, demonstrating that the crucial period of vulnerability extends into early postnatal life in the rat [54]. A reduction in nephron number is observed even when the maternal undernutrition is induced by restriction of only one nutrient in the rat such as protein [7], vitamin A [55], or iron [56], by global food restriction [53], or by a multideficient diet that is rich in carbohydrates that is not deficient in calories [10]. Compensatory glomerular hypertrophy is reported in the neonate rat that exhibits a nephron deficiency of 25% to 30% [53].…”
Section: Maternal Undernutrition and Nephron Numbermentioning
confidence: 99%
“…Especially in preterm infants or those born SGA, optimal early nutrition is important for growth and survival [227]. Through experimental and human studies, it has been shown that postnatal nutrition in terms of calories, protein content, and micronutrients can impact nephron numbers and long-term renal function [15,20,31,82,83,228,229,230]. Animal data suggest some reversal of programmed renal changes can occur with the restoration of normal dietary composition, but overfeeding leads to obesity and hypertension independently of nephron numbers and may therefore be harmful [83,228].…”
Section: Introduction To a Health Problemmentioning
confidence: 99%